A percepção dos professores de educação física de Parintins sobre a Ginástica para Todos - Lima, Stanley Fabricio Simas de (Brasil, 2024)
The practice of Gymnastics for All (GFA) is a set of gymnastics activities that are characterized by being democratic, exclusionary and comprehensive. It is recommended by the National Common Curricular Base in the Physical Education component, specifically in the gymnastics unit. Thus, this study aimed to understand the perception of Physical Education teachers in Parintins about GFA. The research presents itself as descriptive with a qualitative approach and its sample was composed of fourteen Physical Education teachers working in public schools in Parintins. For data collection, a semi-structured interview was used in a face-to-face format and the data was analyzed using the technique of Elaboration Technique and Signified Units Analysis according to Moreira, Simões and Porto (2008) . This technique followed three important moments, which are: ingenuous narration, identification of attitudes and interpretation. As a result of this study, it was possible to identify in the teachers' perception that the absence of the practice of GFA in Physical Education classes is due to four main factors, categorized as follows: weakened formation, lack of structure, lack of pedagogical materials and lack of affinity with the theme. It is noted that GFA is still a gap in the curriculum of Physical Education professionals in Parintins that urgently needs to be filled with specific courses and specializations on the subject, knowing that, during their formative processes, they did not have the contact they should have with practice.